Development of a Health Promotion Model to Improve the Skill Levels of Posyandu Volunteers: A Systematic Literature Review - Kartini Kartini; Siwi Pramatama; Elveira Gamelia (Green Publisher Indonesia, 2026)
Posyandu cadres play a strategic role in supporting community-based primary health services in Indonesia. However, increasingly complex public health challenges require cadres to have broader competencies beyond basic technical skills. Health promotion has been widely recognized as an effective approach to strengthening the capacity and skills of public health volunteers, but studies integrating various components of health promotion into a comprehensive cadre development model are limited. This research aims to identify and synthesize health promotion components that contribute to improving the competence and skills of public health volunteers and develop a health promotion model to improve the skill level of Posyandu cadres. The Systematic Literature Review was conducted following the PRISMA guidelines. Literature searches were conducted using Publish or Perish linked to the Google Scholar database with keywords (